OPTIMIZATION OF CARBON NANOTUBES PRODUCTION FROM PALM OIL WASTE AS SUPERCAPASITOR ELECTRODE - Furqon Nugraha, Nurizal
OPTIMIZATION OF CARBON NANOTUBES PRODUCTION FROM PALM OIL WASTE AS SUPERCAPASITOR ELECTRODE